2014
DOI: 10.1002/qua.24825
|View full text |Cite
|
Sign up to set email alerts
|

The effects of resonance delocalization and the extent of π system on ionization energies of model fluorescent proteins chromophores

Abstract: Recent advances in the design and application of redox-active fluorescent proteins (FPs) stimulated an interest in the electronic structure of the ionized/electron-detached FP chromophores. Here, we report the results of a computational study of the electron-detached and ionized states of model chromophores of green and red FPs. We focus on the analysis of the effects of the phenolate OH group position (ortho, meta, and para) on relative energies of the chromophores in the ground as well as in the ionized/deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…We investigate the electrostatic spectral tuning in both the deprotonated (anionic) and protonated (neutral) forms of p -hydroxybenzylideneimidazolinone (pHBDI), a model compound of the fluorophore of wild-type GFP (see Figure ). Spectral tuning strategies in GFP have primarily focused on chemically modified chromophores, π-stacking, and the protonation state of the phenolate group. As a result, there have been relatively few investigations into the electrostatic spectral tuning mechanism in GFP. , A recent computational study by Kaila et al has investigated the effect of the protein on the absorption spectrum of pHBDI compared to the gas phase . They found that the protein significantly red shifts the absorption of pHBDI relative to the gas phase, and the effect is largely electrostatic.…”
Section: Resultsmentioning
confidence: 99%
“…We investigate the electrostatic spectral tuning in both the deprotonated (anionic) and protonated (neutral) forms of p -hydroxybenzylideneimidazolinone (pHBDI), a model compound of the fluorophore of wild-type GFP (see Figure ). Spectral tuning strategies in GFP have primarily focused on chemically modified chromophores, π-stacking, and the protonation state of the phenolate group. As a result, there have been relatively few investigations into the electrostatic spectral tuning mechanism in GFP. , A recent computational study by Kaila et al has investigated the effect of the protein on the absorption spectrum of pHBDI compared to the gas phase . They found that the protein significantly red shifts the absorption of pHBDI relative to the gas phase, and the effect is largely electrostatic.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with detailed investigations of fluorescent protein chromophores showing that the trend in detachment energy for the series of deprotonated chromophore anions o -HBDI – , m -HBDI – and p -HBDI – , can be explained in terms of the resonance stabilisation of the anion. 65 , 66 This is significant since it has been shown that the trend in redox potentials of a series of equivalent neutral chromophores is determined by the variation in ionisation energy since the solvent effects for structurally similar chromophores are similar. 67 …”
Section: Resultsmentioning
confidence: 99%
“…The IP variations due to structural changes can be explained by several chemical factors such as the mesomeric effect caused for the functional groups and the electronegative and electropositive tendencies in the molecules (Lazzari-Dean, 2015). The increase of IP value in the Pheo_b molecule to Pheo_a and in the Chl_a to Chl_b molecule, due to the substitution of -CH3 to -HC=O functional group can be explained by the presence of the carbonyl group (C=O).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of IP value in the Pheo_b molecule to Pheo_a and in the Chl_a to Chl_b molecule, due to the substitution of -CH3 to -HC=O functional group can be explained by the presence of the carbonyl group (C=O). The C=O is an electron-withdrawing group; therefore, compounds with this functional group tend to attract electrons and their IP value increases (Lazzari-Dean, 2015;Szent-Györgyi, 1968;Tian et al, 2010), the carbonyl group, C=O, being the main carbonyl group of ketones or aldehydes (Szent-Györgyi, 1968). Contrarily, the -OH functional group in the Alloxanthin causes an IP reduction with respect to 𝛼-carotene, as mentioned above.…”
Section: Discussionmentioning
confidence: 99%